Multiplication of Dendrobium Sp Orchid Somatic Embries Using In-Vitro Concentrations of MgSO4 and Myo-Inositol in Murashige and Skoog Media - Jeni Santika; Elfi Indrawanis; Pebra Heriansyah (Jurnal Penelitian Pendidikan IPA, 2023)
Dendrobium Sp orchid is one type of orchid that occupies the top position in ornamental plants. This study aims to determine the administration of various concentrations of magnesium sulfate (MgSO4) and Myo-inositol to Dendrobium Sp orchid explants on Murashige and Skoog media. The design used in this study was a factorial complete randomized design (CRD) consisting of 2 treatment levels (M= MgSO4 and Y= Myo-inositol) with 3 replications. Namely: M0 (without MgSO4), M1 (MgSO4 350 mg/l ), M2 (MgSO4 370 mg/l), M3 (MgSO4 390 mg/l), and Y0 (Without Myo-inositol), Y1 (Myo-inositol 50 mg/l), Y2 (Myo-inositol 100 mg/l) , Y3 (Myo-inositol 150 mg/l). Based on the results of the study, giving various concentrations of magnesium sulfate (MgSO4) alone had a significant effect on all observed parameters, where the best treatment was found in M3 with an average number of shoots 4.04, shoot height 1.08 cm, number of leaves 7.89 fruit, number of roots 6.64 fruit and root length 1.55 cm in Dendrobium Sp. For the treatment of various Myo-inositol concentrations, a single significant effect on all observed parameters, where the best treatment was found in Y3 with an average number of shoots 4.03, shoot height 1.25 cm, number of leaves 7.81, number of roots 4.96 and root length 1.48 in Dendrobium Sp. In interaction, the administration of MgSO4 and Myo-inisitol had a significant effect on all observation parameters, the best treatment was M3Y3 (390 mg/l MgSO4 and 150 mg/l MS Myo-inisitol) namely the number of shoots 4.33, the height of the shoots 1.68 cm, the number of leaves is 8.89, the number of roots is 7.22 cm and the root length is 2.02 cm.